Strengthening Mental Health Literacy and Emotional Regulation among Elementary School Children through the SEHATI Program - Sri Wulan Lindasari; Reni Nuryani; Nunung Siti Sukaesih; Ria Inriyana; Heri Ridwan; Putri Kamilah (Jurnal Medika: Medika, 2026)
Mental health is a crucial aspect of a child’s development. It directly impacts academic progress, social relationships, and the ability to manage emotions in a healthy way throughout life. During elementary school, children begin to face academic demands, complex social interactions, and significant emotional changes. Low mental health literacy limits their ability to recognize, express, and manage emotions in an adaptive manner. Children tend to express stress through external behaviors (easily angered, withdrawing, difficulty concentrating) that are often not recognized as early indicators of mental health issues. Approximately 10–20% of school-aged children experience emotional problems that impact learning and social functioning, with higher prevalence among migrant and diaspora children. This community service initiative aims to improve mental health literacy and emotional regulation through the SEHATI (Sekolah Hati Sehat) program. The method used is a participatory educational approach with stages of needs analysis, program implementation, and evaluation. The study subjects consisted of 27 elementary school students and 6 teachers. The instruments used were pre-test and post-test questionnaires. The results showed an increase in the average mental health literacy score among students from 71.3 to 88.6, as well as an increase in the emotional regulation score from 67.6 to 78.4. This indicates that the SEHATI program is effective in improving mental health literacy and strengthening emotional regulation among elementary school students